2020
DOI: 10.1007/s00396-020-04707-3
|View full text |Cite
|
Sign up to set email alerts
|

Experimental and theoretical studies of benzoquinone modified poly(ortho-phenylenediamine): singlet oxygen generating oligomers

Abstract: The present work reports microwave-assisted polymerization of 1,4-benzoquinone with ortho-phenylenediamine for the effective generation of singlet oxygen ( 1 O 2 ). The oligomeric structures were confirmed by the experimental IR, 1 H-NMR, ultravioletvisible and TEM analyses. The theoretical IR and UV data were computed using DFT/B3LYP method with 6-311G basis set, and the 1 H-NMR spectra were computed by gauge-independent atomic orbital (GIAO) method. The experimental IR, 1 H-NMR, and UV studies were found to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 26 publications
0
5
0
Order By: Relevance
“…They proposed that their findings could be useful in the application of engineered oligomers as photosensitive probes for photodynamic treatment. 155 Singh et al also reported novel azo benzene functionalized aniline, 1-naphthylamine, luminol and o -phenylenediamine prepared by using an ultrasound technique. The researchers suggested that the synthesized polymers also showed high singlet oxygen generation characteristics.…”
Section: Utilizing Conjugated Polymers Copolymers and Nanocomposites ...mentioning
confidence: 99%
“…They proposed that their findings could be useful in the application of engineered oligomers as photosensitive probes for photodynamic treatment. 155 Singh et al also reported novel azo benzene functionalized aniline, 1-naphthylamine, luminol and o -phenylenediamine prepared by using an ultrasound technique. The researchers suggested that the synthesized polymers also showed high singlet oxygen generation characteristics.…”
Section: Utilizing Conjugated Polymers Copolymers and Nanocomposites ...mentioning
confidence: 99%
“…Lately, Riaz et al 78 have reported the theoretical IR and UV data of 1,4-benzoquinone with ortho -phenylenediamine using the DFT/B3LYP method with the 6-311G basis set, and the 1 H-NMR spectra were computed by the gauge-independent atomic orbital (GIAO) method (Fig. 12).…”
Section: Computational Studies On Miscellaneous Conducting Polymersmentioning
confidence: 99%
“…Optimizations of PTh/BQ geometries were carried out without symmetry constraints by using hybrid functional DFT/B3LYP method with 6-311G basis set. [13][14][15] The geometric optimization was carried out by taking 3 units of thiophene, coupled with 3 units of benzoquinone/ hydroquinone. The frequency calculations (IR spectra) were computed by using same method, while the electronic transitions were calculated by using the time-dependent DFT (TD-DFT) method with 6-311G basis set.…”
Section: Computational Studiesmentioning
confidence: 99%
“…The quantum yields (F) were calculated as per the reported method by using Rhodamine B as a reference. [13][14][15] .…”
Section: Fluorescence Emission and Confocal Studiesmentioning
confidence: 99%